Thérèse Raquin d’Émile Zola : la notion de tempérament entre l’héritage antique et l’apport de la physiologie du XIXe siècle - Kaczmarek-Wiśniewska, Anna (Studia Romanica Posnaniensia, 2020)
Therese Raquin, Zola’s first important work, is based on the modern version of the old physiological theory of “temperaments”, e.g. the combination of four cardinal “humours” that determine a man’s physical and mental constitution. Through the story of two murderers, an adulterous woman and her lover who kill the woman’s husband, the author shows the mutual influence of two temperaments considered in the 19th century as more important than all the others: sanguine and melancholic (or nervous). The novel intends to “verify” a theory dealing with the consequences of each type of temperament for people’s behaviour, their relationships and their internal life.